2015
DOI: 10.2174/0929867322666150114152421
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Brain Hemorrhage (NBH) of Prematurity: Translational Mechanisms of the Vascular-Neural Network

Abstract: Neonatal brain hemorrhage (NBH) of prematurity is an unfortunate consequence of preterm birth. Complications result in shunt dependence and long-term structural changes such as post-hemorrhagic hydrocephalus, periventricular leukomalacia, gliosis, and neurological dysfunction. Several animal models are available to study this condition, and many basic mechanisms, etiological factors, and outcome consequences, are becoming understood. NBH is an important clinical condition, of which treatment may potentially ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 428 publications
(408 reference statements)
1
28
0
1
Order By: Relevance
“…Wang et al found no association between neonatal risk factors, including grade III–IV intraventricular hemorrhage, and restless sleep in children born EPT at the age of 18–22 months ( 44 ). However, our findings were not unexpected since both cerebral hemorrhage and SGA are known risk factors for adverse neurodevelopmental outcomes ( 16 , 45 ), and since we previously reported that a variety of sleep problems are more prevalent in EPT children with neurodevelopmental disabilities ( 10 ). Previous studies show that to be SGA add to the risk for several types of morbidity for EPT children ( 46 ).…”
Section: Discussionsupporting
confidence: 68%
“…Wang et al found no association between neonatal risk factors, including grade III–IV intraventricular hemorrhage, and restless sleep in children born EPT at the age of 18–22 months ( 44 ). However, our findings were not unexpected since both cerebral hemorrhage and SGA are known risk factors for adverse neurodevelopmental outcomes ( 16 , 45 ), and since we previously reported that a variety of sleep problems are more prevalent in EPT children with neurodevelopmental disabilities ( 10 ). Previous studies show that to be SGA add to the risk for several types of morbidity for EPT children ( 46 ).…”
Section: Discussionsupporting
confidence: 68%
“…The germinal matrix has many growing and dividing neuronal and glial precursor cells. Prior GMH studies have documented increased proliferative cytokines and pathways, such as TGF-β and mTOR, after injury, and we speculate proliferative signaling triggers more profound gliosis after neonatal brain hemorrhage (Lekic et al, 2015). While brain cell death is definitely occurring, we speculate proliferative signaling in conjunction with increased leukocyte infiltration contributes towards these observed results in neonatal brains.…”
Section: Discussionmentioning
confidence: 63%
“…The consequent hematoma applies mechanical pressure to glia and neurons, resulting in cytotoxicity and necrosis, as well as evokes an inflammatory response, leading to secretion of destructive proteases and oxidative species (Lekic et al, 2015). In adult cerebral hemorrhage, clinical studies indicate hematoma volume is the best prognostic indicator; larger hematoma volumes have worsened outcomes (Keep et al, 2005; Xi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Lekic et al [18] stated that early implantation of a VP shunt for the treatment of PHH is the method of choice. However, the VP shunt implantation can also bring many complications.…”
Section: Management Of Phhmentioning
confidence: 99%